Unveiling Ruthenium(II) Diazadienyls for Gas Phase Deposition Processes: Low Resistivity Ru Thin Films and Their Performance in the Acidic Oxygen Evolution Reaction - David Zanders; Jorit Obenlüneschloß; Jan‐Lucas Wree; Julia Jagosz; Parmish Kaur; Nils Boysen; Detlef Rogalla; Aleksander Kostka; Claudia Bock; Denis Öhl; Michael Gock; Wolfgang Schuhmann; et al. (Advanced Materials Interfaces, 2022)
Abstract Two novel ruthenium complexes belonging to the Ru(II)(DAD)(Cym) (DAD = diazadienyl) (Cym = cymene) compound family are introduced as promising precursors. Their chemical nature, potential for chemical vapor deposition (CVD), and possibly atomic layer deposition (ALD) are demonstrated. The development of nonoxidative CVD processes yielding high‐quality Ru thin films is realized. Chemical analyses are exercised that vitiate the deceptive assumption of Ru(DAD)(Aryl) complexes being zero‐valent through clear evidence for the redox noninnocence of the DAD ligand. Two different CVD routes for the growth of Ru films are developed using Ru(tBu2DAD)(Cym). Ru thin films from both processes are subjected to thorough and comparative analyses that allowed to deduce similarities and differences in film growth. Ru thin films with a thickness of 30–35 nm grown on SiO2 yielded close‐to‐bulk resistivity values ranging from 12 to 16 µΩ cm. Catalysis evaluation of the films in the acidic oxygen evolution reaction (OER) results in promising performances based on overpotentials as low as 240 mV with Tafel slopes of 45–50 mV dec−1. Based on the degradation observed during electrochemical measurements, the impact of OER conditions on the layers is critically assessed by complementary methods.